2017
DOI: 10.1186/s12890-017-0499-y
|View full text |Cite
|
Sign up to set email alerts
|

Medical thoracoscopy for exudative pleural effusion: an eight-year experience from a country with a young population

Abstract: BackgroundWith the exception of areas with high prevalence of tuberculosis, medical thoracoscopy is becoming the diagnostic modality of choice for exudative pleural effusions. The aims of this study were to determine the diagnostic yield and safety of medical thoracoscopy for exudative pleural effusions and ascertain the etiology of such effusions in Qatar.MethodsThis is a retrospective-descriptive study of 407 patients who underwent diagnostic medical thoracoscopy for exudative pleural effusions from January,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
4
16
0
1
Order By: Relevance
“…However, the currently available evidence supporting this approach is limited [7]. We have shown in a previous study from this country that sago-like nodules to be among the most common Journal of Tuberculosis Research findings on gross thoracoscopic appearance of TPE cases (seen in 51% of cases) [8]. Similar results have also been reported by other investigators [7].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the currently available evidence supporting this approach is limited [7]. We have shown in a previous study from this country that sago-like nodules to be among the most common Journal of Tuberculosis Research findings on gross thoracoscopic appearance of TPE cases (seen in 51% of cases) [8]. Similar results have also been reported by other investigators [7].…”
Section: Introductionsupporting
confidence: 86%
“…onstration of MTB bacilli in biopsy specimens is not an absolute requirement for making TPE diagnosis and the presence of caseating granulomatous inflammation in high burden sittings is considered adequate[4] [6][16]. In the State of Qatar, TB is a common health problem with an incidence of 40/100,000 populations per year and is the most common etiology of exudative pleural effusions accounting for 84.5% of cases[8]. About 97% of TB patients are expatriates (mostly from Asian countries with high TB prevalence)[17].…”
mentioning
confidence: 99%
“…These granulomatous lesions may grossly present as sago-like lesions in the pleura. A recent study demonstrated that sago-like nodule is the most common gross pleuroscopic nding in TB pleural effusion [18]. Our results were consistent with this nding and showed that sago-like nodule was observed in more than 70% of the patients with TB pleurisy.…”
Section: Discussionsupporting
confidence: 92%
“…Medical thoracoscopy is an excellent diagnostic modality for exudative pleural effusion, and its yield in tuberculosis is very high. 2…”
Section: Discussionmentioning
confidence: 99%